Analysis of Sago Contribution as Staple Food Alternatives to Household Food Security - Andi Tenri Fitriyah; Baharuddin Baharuddin; Aylee Christine Alamsyah Sheyoputri (Journal of Global Innovations in Agricultural Sciences, 2025)
This present study attempted to discuss the changing consumption patterns of Sago and rice in Pancakarsa village, Mangkutana District, East Luwu Regency, South Sulawesi, with a focus on the contribution of Sago to household food security. Rice has replaced Sago as the preferred staple food among the local community, but Sago still has an essential value as a traditional and alternative basic food item. The study aims to understand Sago's role as a household basic food comprehensively. Data were collected through interviews with 15 respondents (representing 152 households) employing quantitative descriptive analysis. The analyzed data consisted of primary data from interviews with respondents and secondary data from relevant institutions, including village officials and the Central Bureau of Statistics. The results demonstrated that the educational degree of respondents ranged from Primary School (66.7%), Junior High School (26.7%), to Senior High School (2.67%). Sago's contribution to household basic food security is classified as moderate, while rice is in the high category. The theoretical and managerial implications of these findings are discussed in the present study. Some Sago-based traditional food products produced by Pancakarsa villagers included Kapurung, Sinole, Dange, Bagea, Ongol-ongol, and Cendol. These carbohydrate sources contain good nutrition. Promoting Sago as local food may also be linked to efforts to maintain food diversity and environmental sustainability. Keywords: Food consumption pattern, household food contribution, household, rice, Sago .